Genetic Research to Guide Conservation and the Understanding of Freshwater Eels of the Genus Anguilla: A Bibliographic Analysis - Miller, Therese; Miller, Michael; Giles, Emily; Jeffs, Andrew; Sabadel, Amandine; Laroche, Olivier; Pochon, Xavier (Canadian Science Publishing, 2026)
Anguillid eels have facultative catadromous life histories that include long distance oceanic spawning migrations and an extensive leptocephalus larval duration. Less known is the important role genetic research has played in understanding these mysterious fishes of the genus Anguilla. A bibliographic literature search was conducted on studies using genetic methodologies to understand Anguilla species, and a database of papers from 1973–2025 included 335 publications, increasing over time to reach a maximum of 103 between 2020 and 2025. The DNA literature was dominated by studies on Anguilla, Anguilla, and Anguilla, but all species have been included in recent phylogenetic studies. In addition to providing a bibliographic database of genetic papers, this review points to the value of multi-gene or whole genome approaches to clarify relationships within and among anguillid eel species. There is also the need for the development of standardised protocols for environmental DNA (eDNA) research with improved species-specific assays, which can help support the conservation of these remarkable fishes that live in both freshwater and the sea.
Keywords: 31 Biological Sciences; 3105 Genetics; Genetics; 15 Life on Land; 0602 Ecology; 0608 Zoology; 0704 Fisheries Sciences; Fisheries; 3005 Fisheries sciences; 3103 Ecology